Pengembangan Media Lupas (Ludo IPAS) di Kelas IV SD Negeri 28 Pontianak Selatan - Novada, Cristine; Kartono, Kartono; Salimi, Asmayani (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study aims to develop and produce valid, practical and effective Lupas (Ludo IPAS) learning media by using the type of research and development (Research and Development), using mixed methods (mix methods) and the ADDIE model, namely analysis, design, development, implementation, and evaluation. Implementation was carried out at SDN 28 South Pontianak on Class IV students as many as 27 respondents. The results of the research are in the form of Lupas (Ludo IPAS) media product development in learning